Lesser States And Multinational Companies: Studi Kasus Terhadap Implikasi Keberadaan Perusahaan H&M Di Industri Fast Fashion Bangladesh - Innesia Ma’sumah; Indra Kusumawardhana (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2020)
Abstract This article probes to understanding the dynamics of multinational companies (MNC) versus least developed countries (LDC). The multinational company that is the object of this study is H&M, which has a base in Sweden as a home country. Then, this study focuses on H&M with its phenomenon of fast fashion, penetrating into Bangladesh and making it a host country to run the clothing production process to meet global consumption. Bangladesh itself is a least developed country whose national economic growth, especially in the export sector, is highly dependent on the garment industry. Therefore, this study will try to answer the phenomenon of the role of H&M in Bangladesh with the research question what are the implications of the growing H&M industry for workers in Bangladesh in 2005-2011? This problem will be seen through the lens of international political economy (IPE) with a focus on the interaction of multinational companies and less developed countries. Keywords: MNCs, LDCs, H&M, Bangladesh, Fast Fashion